Faktor yang Mempengaruhi Niat Mengadopsi Usahatani Sayuran Organik di Kecamatan Getasan Semarang - Vaniamon Wira Yasyak; Suhatmini Hardyastuti; Slamet Hartono (Universitas Gadjah Mada, 2020)
Organic farming has attracted increasing attention in recent decades. Many believe this is necessary to maintain agricultural production while addressing environmental damages caused by conventional farming methods. However, the adoption of organic vegetable farming in Indonesia is still fairly slow. The fact that only a small number of farmers adopt organic farming begs explanation. Studies have shown that intention determines human behaviors. The problem is that intention to choose organic farming does not always manifest in behavior. To address this problem it is helpful to consider three factors affect how intention manifest in behavior, namely attitudes, subjective norms, and behavioral control. Based on in the case study on the central vegetable farming area of Kopeng village where conventional farming is still dominant, this paper analyzes the intention organic farmers in the light of the theory of planned behavior. Applying the SEM-PLS model of analysis, it identifies the key-driver organic farmers. This study found that farmers’ positive attitude toward organic farming is not the main drive in their shift from non-organic to organic farming. Rather than subjective norms, behavior control has the greater influence on the farmers’ choice to adopt organic vegetable farming. Famers view organic agriculture positively; but the main obstacle is the access to information about organics, certification capabilities and other aspects of behavioral control which make adoption rate for organic vegetable farming is still low.